Acute Abdominal Pain in Young Versus Elderly Patients: A Comparative Prospective Study of Clinical Presentation, Aetiology, and Management Outcomes - Hayder Hasan Hadi; Abdulhadi Jabbar Sarhan (Journal of Biomedicine and Biochemistry, 2026)
Background: Acute abdominal pain is a common emergency presentation. Clinical features, aetiology, and outcomes differ markedly between young and elderly patients. Objectives: To compare presentation, diagnosis, management, and outcomes of acute abdominal pain between young (<60 years) and elderly (≥60 years) patients. Patients and Methods: A prospective study of 193 patients at Al-Hussain Teaching Hospital, Nasiriyah, Iraq (January–November 2024). Group A: young (<60 years, n=139); Group B: elderly (≥60 years, n=54). Results: Acute appendicitis predominated in young patients (51.80% vs. 16.67%, p<0.001). Perforated duodenal ulcer (27.78% vs. 7.19%, p=0.018) and intestinal obstruction (24.07% vs. 4.32%, p<0.001) were more frequent in the elderly. Young patients more often had tenderness, right iliac fossa pain, and rigid abdomen, while constipation and distension were commoner in elderly patients. Appendectomy was performed more in young patients (51.80% vs. 11.11%, p<0.001); conservative management predominated in the elderly (72.22% vs. 33.09%, p<0.001). UTI complications were significantly higher in elderly patients (9.26% vs. 0.72%, p=0.012). Conclusions: Elderly patients present atypically with higher rates of serious pathology and postoperative complications. Age-stratified protocols are essential to optimize outcomes.